Pengembangan Lembar Kerja Siswa Matematika Berbasis PMRI dengan menggunakan Qr Code pada Siswa Kelas V Sekolah Dasar - Novianti Mandasari; Aswarliansyah Aswarliansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this project is to provide reliable, usable, and efficient PMRI-based Student Worksheets (LKS) for the fifth grade mathematics curriculum at SD N 13 Rejang Lebong. The 4D development model is used in this study together with the research and development methodology. There were 54 fifth graders at SD N 13 Rejang Lebong who served as the research participants. The analysis's findings demonstrated that the student worksheets, which had an average score of 0.86 (V> 0.8), were classified as legitimate. LKS falls into the very practical category with an average score of 4.04 and a maximum score of X> 3.4, making it very practical. Based on the results of the pretest and posttest completed by the students, it can be concluded that LKS is classified as Effective since N-gain(g) of 0.70 is included in the interval category g> 0.7 with high categorization. Keywords : LKS, PMRI, Qr Code